Isolation and characterization of indigenous copper resistant bacteria from Yogyakarta tannery factory waste - Wahyu Irawati; Polin Parulian Ambarita; Desi L. Sihombing; Vannesa El Shaday Ruth Advenita; Eunike Bunga Marvella (Jurnal Biologi Tropis, 2022)
The leather tanning industry is one of the industries that causes environmental damage because one of the processes uses copper to produce products such as bags, jackets, and shoes. Copper bioremediation using indigenous bacteria is an effective solution to the problem of pollution because it utilizes bacteria isolated from the polluted environment. This study aims to isolate and characterize copper-resistant bacteria from the waste of the Yogyakarta Tannery Industry. The medium used was Luria Bertani Agar with the addition of 3 mM CuSO4. The characterization carried out included the characterization of colony and cell morphology such as color, edges, optical appearance, cell shape, and Gram staining. The isolation results obtained eight isolates of copper-resistant bacteria, namely Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8. Isolates Y1, Y2, Y3, Y4, Y5, and Y8 were Gram positive bacteria while isolates Y5 and Y6 were Gram negative bacteria. Colonies of isolates Y1, Y3, Y4, Y8 greenish color indicates the accumulation of copper in the cells as a mechanism of resistance. The discovery of isolates of copper-resistant bacteria from samples of the tannery industry waste is a useful study as an initial study to obtain isolates of Indonesian indigenous copper-resistant bacteria to be further developed as a copper bioremediation agent in the treatment of copper waste in the leather tanning industry.